Governance: Informal food markets in Africa’s cities - Resnick, Danielle (International Food Policy Research Institute, 2017)
Urbanization is moving fastest in Africa south of the Sahara, with major implications for food security and other governance challenges. Large urban poor populations rely heavily on the informal economy for accessible, affordable food. Most eggs, meat, fish, and milk sold to the urban poor are from informal markets. Food security policies in urban Africa face institutional, administrative, and political challenges: Lack of local mandate for food security under decentralization policies. Lack of cross-sectoral, cross-ministerial policy integration. Political contest over cities that occasionally leads to violence. Government interventions have focused on control, regulation, and often violent eradication of the urban informal food economy.